Multidetector-row CT imaging evaluation of superior and inferior vena cava normal anatomy and caval variants: Report of our cases and literature review with embryologic correlation. (March 2019) - Iezzi, Roberto; Posa, Alessandro; Carchesio, Francesca; Manfredi, Riccardo
Objective: To assess the potential of multidetector-row computed tomography imaging and its reformations in the evaluation of the superior and inferior vena cava normal anatomy and their anatomical variants, and to make a brief review of caval embryogenesis and developmental errors. Methods: We retrospectively reviewed a total of 1000 whole-body computed tomography scans performed between January 2010 and December 2016 to assess the normal superior and inferior vena cava anatomy and their variants. Results: The normal superior and inferior vena cava anatomy was found in 88.9% of patients, whereas multiple variants were found, ranging from the superior or inferior vena cava duplication, to the azygos continuation of the inferior vena cava. Conclusions: Computed tomography is a powerful tool to analyse superior and inferior vena cava anatomical variants. The knowledge and assessment of normal caval anatomy and of its anatomical variants is mandatory in the correct pre-operative planning in surgical and radiological interventions. Knowledge of caval variants is helpful in the differential diagnosis of abdominal or mediastinal masses, to avoid misdiagnosis, as well as in the screening of associated congenital pathologic conditions.